DEKONSTRUKSI IDEOLOGI PENDIDIKAN DALAM KARYA SASTRA (NOVEL) - Rico Aprisa (STKIP ROKANIA, 2016)
This study focuses on the analysis of the ideological deconstruction of education in novel. The main character is experiencing an inner conflict in ideology education, where one side of the main character wants to fulfill his desire choose public school he wants, on the one hand should be against the wishes of his parents. Through the story the main character is this phenomenon of education and ideology in the novel happen, and in the context of today's global society